Engineering mathematics-I : makaut-2018 - Kar, Sourav (McGraw Hill Education(I), 2019)
Engineering mathematics-I : makaut-2018 / Kar, Sourav. -- Chennai: McGraw Hill Education(I), 2019 510 K18 No. of Copies : 1